2010
DOI: 10.4269/ajtmh.2010.09-0467
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 Polymorphisms Are Associated with Altered IFN-γ Levels in Children with Cerebral Malaria

Abstract: Abstract. Toll-like receptor (TLR) polymorphisms have been associated with disease severity in malaria infection, but mechanisms for this association have not been characterized. The TLR2, 4, and 9 single nucleotide polymorphism (SNP) frequencies and serum interferon-γ (IFN-γ) and tumor necrosis factor-α (TNF-α) levels were assessed in Ugandan children with cerebral malaria (CM, N = 65) and uncomplicated malaria (UM, N = 52). The TLR9 C allele at −1237 and G allele at 1174 were strongly linked, and among child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
5
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 49 publications
3
34
5
3
Order By: Relevance
“…In order to verify the genetic contributions of these variants to malaria with more precision, we performed a comprehensive search and pooled the results of independent studies for meta-analysis. Our meta-analysis results for the TLR4D299G variant were consistent with those of previous studies on diverse ethnicities from different malarial endemic regions 2,20,22 , with no difference in the genotype or allele frequency distributions of the D299G polymorphism between UM and SM subjects. Although the contribution of the 299G minor allele has been controversial in children 7,20,22,23 , adult studies show no association 2,21,24 with the exception of maternal anemia in pregnant women 25 .…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In order to verify the genetic contributions of these variants to malaria with more precision, we performed a comprehensive search and pooled the results of independent studies for meta-analysis. Our meta-analysis results for the TLR4D299G variant were consistent with those of previous studies on diverse ethnicities from different malarial endemic regions 2,20,22 , with no difference in the genotype or allele frequency distributions of the D299G polymorphism between UM and SM subjects. Although the contribution of the 299G minor allele has been controversial in children 7,20,22,23 , adult studies show no association 2,21,24 with the exception of maternal anemia in pregnant women 25 .…”
Section: Discussionsupporting
confidence: 79%
“…Although some studies have reported no association between T-1486C and malaria susceptibility or severity 7,20,22,24,27,30 , we observed that the -1486C allele was a risk factor for severe malaria and high parasite load, which is in line with previous findings 21,24 . Moreover, -1486C has been associated with an increased risk of low birth weight in term infants born to P. falciparum-infected pregnant women 25 .Consistent with these findings, the meta-analysis of the T-1486C variant revealed a significant association with SM under the allele contrast (T vs. C) and homozygous (TT vs. CC) genetic models.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Therefore the significance if any, of the detection of malaria products by TLR2 and TLR9 to the development of CM is currently unknown. However despite the conflicting data regarding TLRs in murine models of CM, a polymorphisms in TLR9 has been associated with altered levels of IFNγ in children with CM [92].…”
Section: T Cells Cd11c+ Dendritic Cells and The Increased Expressionmentioning
confidence: 99%